Peran Program Repatriasi Dalam Peningkatan Mutu Pendidikan di Community Learning Center (CLC) Sabah Malaysia - Lia Anggraeni; Nurtanio Agus Purwanto (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: The study aims to examine the role of repatriation programs in improving the quality of education in Community Learning Centers (CLCs) in Sabah, Malaysia. The main focus of the research is to investigate the aspects of education quality in CLCs, identify obstacles to improving the quality of education in CLCs, understand the implementation of repatriation, and identify the role of repatriation programs. This research is expected to provide strategic recommendations to improve the quality of education in CLCs in Sabah, Malaysia. This research was descriptive research with a qualitative approach. The location of this research was CLC in the Sabah, Malaysia, region. The subjects in this study were the principal of the Indonesian School of Kota Kinabalu (SIKK), CLC teachers, and CLC alumni. Data collection in this study was carried out by technical observation, documentation, and interviews. The validity of the data was checked using a triangulation technique. Meanwhile, data analysis used qualitative data analysis techniques (Miles and Huberman), with the stages of data collection, data reduction, data presentation, and conclusion drawn. The study shows that each CLC seeks to meet the eight national education standards set by the Indonesian government. Because the SNP has not been implemented optimally, SIKK as the parent school of CLC carries out internal standardization through monitoring and evaluation. Obstacles to improve the quality of CLC education are mostly in terms of administration. Besides that, each CLC has different challenges and obstacles. The repatriation program is one of the efforts to improve quality in the form of repatriation of students to continue their education, which is divided into the ADEM repatriation pathway, which is fully financed by the government, and the Foundation repatriation pathway, which the Foundation or partner schools finance. The role of the repatriation program in improving the quality of education in CLC, Sabah, Malaysia, includes increasing students' motivation to learn, increasing parents' awareness of education, improving the quality of CLC graduates, and improving the quality of the educational service process at CLC. Keywords: CLC; quality of education; repatriation Abstrak: Penelitian ini bertujuan untuk mengkaji peran program repatriasi dalam peningkatan mutu pendidikan di Community Learning Center (CLC) di Sabah, Malaysia. Fokus utama penelitian adalah mengetahui aspek mutu pendidikan yang ada di CLC, mengidentifikasi hambatan dalam peningkatan mutu pendidikan di CLC, mengetahui pelaksanaan repatriasi serta mengidentifikasi peran program repatriasi. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Lokasi penelitian ini adalah CLC di wilayah, Sabah, Malaysia. Subjek dalam penelitian ini adalah Kepala Sekolah Indonesia Kota Kinabalu (SIKK), Guru CLC dan Alumni CLC. Pengumpulan data dalam penelitian ini dilakukan dengan teknik observasi, dokumentasi dan wawancara. Pemeriksaan keabsahan data dilakukan dengan teknik triangulasi. Sedangkan analisis data menggunakan tahap pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Penelitian ini menghasilkan temuan diantaranya setiap CLC berupaya memenuhi delapan standar nasional pendidikan yang ditetapkan oleh pemerintah Indonesia. Dikarenakan SNP tidak diterapkan secara maksimal, SIKK sebagai sekolah induk bagi CLC melakukan standarisasi internal melalui monitoring dan evaluasi. Hambatan dalam peningkatan mutu pendidikan CLC sebagian besar dari segi administrasi, selain itu masing-masing CLC memiliki tantangan dan kendala yang berbeda. Program repatriasi menjadi salah satu upaya dalam peningkatan mutu dengan bentuk pemulangan peserta didik untuk melanjutkan pendidikan yang terbagi atas jalur repatriasi ADEM dan jalur repatriasi Yayasan. Peran program repatriasi dalam peningkatan mutu pendidikan di CLC, Sabah, Malaysia diantaranya meliputi meningkatkan motivasi belajar peserta didik, meningkatkan kesadaran orang tua tentang pendidikan, meningkatkan mutu lulusan CLC dan meningkatan mutu proses layanan pendidikan di CLC. Kata kunci: CLC; mutu pendidikan; Repatriasi